RELATIONSHIP BETWEEN ORGANIZED CRIME AND VIOLENT RADICALIZATION - Teodor FRUNZETI; Iulia-Mihaela DRĂGAN (Annals: Series on Military Sciences, 2025)
Organized crime became a problem of international interest for law enforcement authorities and security field from the perspective of its transnational nature and the areas in which it can manifest itself: drug trafficking, arms trafficking, human beings or cultural relics. On the other hand, violent radicalization is a phenomenon that security institutions are making efforts to combat considering the security risks generated by this manifestation: political violence or terrorism. The purpose of this research is to extract the similarities and differences between the two phenomena, using comparative analysis as a methodology. The research question targeted by this study refers to the identification of the relationship between the two phenomena, as well as the connecting elements.